Peach Breeding in Spain - Llácer, Gerardo; Badenes, María L.; Alonso, J. M.; Rubio-Cabetas, María J.; Batlle, Ignasi; Vargas, F. J.; Iglesias, Ignasi; García-Brunton, Jesús (2017)
Peach is the main stone fruit grown in Spain. The area devoted to this crop has increased slightly over the past 15 years, however its production has doubled in this period. Spain ranks fourth in the world production after China, Italy and the USA, producing 25% of the total peach crop in the European Union. Although peach production increases, consumption in Spain has decreasing as occurs in other western countries. The lack of internal fruit quality is the main reason claimed by consumers for declining to buy fresh peaches. In addition to fruit quality, the main limitations of this crop are: poor adaptability of many cultivars from foreign countries to the Spanish environment, the dependency from cultivars bred in other countries, the incidence of pests, diseases and abiotic stresses and the high cost of the crop management. These problems can be overcome, in part, by developing breeding programs based on controlled crosses. The Spanish peach breeding programs have the following main objectives: - Fruit quality: many cultivars, mainly the early cultivars, have a good external quality but they lack internal quality. - Adaptability to the environment and a better harvest calendar. There is an increase of cultivars with low or very low chilling requirements which allows to grow peaches in warm climates and to advance harvest season more than 30 days. The aims are to breed for early cultivars in Andalucia, Murcia, Valencia and Extremadura; late cultivars in Aragon; and to extent the harvest season in Aragon, Cataluna and Extremadura. - Resistance or tolerance to pests and diseases: resistance to aphids and fungal diseases like Sphaerotheca pannosa (powdery mildew), Monillia spp. and Taphrina deformans (leaf curl). - To avoid dependency from the foreign materials, which implies to pay royalties and some times have a worse adaptability.